Do cultural characteristics affect investigation? - Li, Wen-Chin; Young, Hong-Tsu; Wang, Thomas; Harris, Don (Cranfield University, 2009)
Separating the people from the problem assumes an individualist value set underlying the Western approach to investigation. In collectivist cultures, where relationships prevail over tasks, this is an almost impossible demand. Effective investigation for aviation accidents within different cultural contexts demands insight into the range of cultural values to be expected among partners from other countries, in addition to an awareness of the investigator’s own culturally determined values. Effective international investigations also demand language and communication skills to guarantee that the messages sent to the other professional investigators from different cultures with different approaches to accident investigation will be understood in the way they were meant to be. The global interaction between different cultures involves sharing the values of all partners. It is important to know more about the similarities and differences in culture-influenced accident investigation philosophies, e.g., when European and Asian culture collaborate together. The cognitive orientation and mechanisms of Eastern and Western cultures are sufficiently different that they may draw completely different inferences from the same set of data (as in this case), especially in the case where human factors are concerned. The best approach may be to try to understand the events in the accident from the viewpoint of the culture of the pilots/airline involved in the accident and not from the cultural viewpoint of the investigator. This way there might be a better chance that culturally congruent remedial actions can be proposed. However, by better understanding these cultural differences it seems highly likely that they can only serve to complement and enrich each other.
Keywords: Accident Investigation, Aviation Safety, Cross-cultural research, Human Factors Analysis and Classification System